Wasathiyyah Sebagai Pilar Peradaban - Muhammadun Muhammadun (Lembaga Penerbitan dan Publikasi Ilmiah IAI Bunga Bangsa Cirebon, 2020)
Sharia has the aim of bringing convenience and eliminating distress. Through the concept of wasathiyyah (moderation) it is not permissible for muftis, judges or legal experts to choose severe decisions in cases where lighter alternatives can be sought. According to Wahbah az-Zuhaili, this concept can be realized by considering a balanced person's rights and obligations towards others, the material and spiritual world; a balance between forgiveness and resistance, sympathy and hatred for extremism in all its forms. The root of almost all social problems is a constant deviation from this path. It is Wasathiyyah who is most likely to bring stability and calm. Because he is a manifestation of the essence of moral honor and glory of Islam. Furthermore, Islam also promotes these values ​​not only among Muslims, but also in their relations with other religious communities and nations. So that wasathiyyah, is a pillar and preserver of civilization Abstrak Syariah memiliki tujuan untuk membawa kemudahan serta menghilangkan kesusahan. Melalui konsep wasathiyyah (moderasi) tidak boleh bagi mufti, hakim atau ahli hukum memilih putusan berat pada kasus-kasus yang dapat dicari alternatif lebih ringan. Menurut Wahbah az-Zuhaili> konsep tersebut dapat diwujudkan dengan mempertimbangkan secara seimbang hak dan kewajiban seseorang terhadap orang lain, dunia material dan spiritual ; keseimbangan antara memaafkan dan melakukan perlawanan, simpatik dan kebencian terhadap ekstrimisme dalam segala wujudnya. Akar pada hampir semua masalah sosial adalah selalu adanya penyimpangan dari jalan ini. Wasathiyyah lah yang paling mungkin membawa stabilitas dan ketenangan. Karena ia merupakan wujud dari esensi kehormatan moral dan kemuliaan Islam. Lebih lanjut, Islam juga menyerukan nilai-nilai tersebut tidak hanya di kalangan kaum muslimin, namun juga dalam hubungan mereka dengan komunitas agama dan bangsa lain. Sehingga wasathiyyah, merupakan pilar dan pemelihara peradaban